Rancang Bangun Alat Penetas Telur dengan Sistem Pengendali Suhu dan Kelembapan Menggunakan Metode Fuzzy dan Monitoring Berbasis IoT: Rancang Bangun Alat Penetas Telur dengan Sistem Pengendali Suhu dan Kelembapan Menggunakan Metode Fuzzy dan Monitoring Berbasis IoT - Wendy Kriswanto Simangunsong; Manurung, Cyntya Tri Hartati; Suciningtyas, Ika Karlina Laila Nur (JURNAL INTEGRASI, 2025)
The egg hatching process is an important stage in the poultry farming industry that requires optimal temperature and humidity control. This research develops an automatic egg hatcher equipped with Mamdani fuzzy logic-based control and Internet of Things (IoT)-based monitoring. The fuzzy system is used to precisely regulate temperature and humidity, while IoT technology enables real-time monitoring through a digital platform. The test results show high accuracy with an average error of 0.78% for temperature and 1.08% for humidity. IoT monitoring has reliable performance with a data transmission delay of 5-7 seconds. In addition, it achieved 71,4% hatchability, proving its effectiveness in creating optimal environmental conditions for hatching. It provides a modern solution that improves the efficiency, productivity, and quality of hatching eggs, and makes it easier for farmers to monitor and control the process automatically.